Monetary Policy Reform in a World of Central Banks - Gunther Schnabl (Graduiertenkolleg 'Konstitutionelle Grundlagen globalisierter Finanzmärkte - Stabilität und Wandel', 2012)
The paper identifies based on the monetary overinvestment theories by Wicksell (1898), Mises (1912) and Hayek (1929) monetary policy mistakes in large industrial countries issuing international currencies. It its argued that a neglect towards monetary policy reform in a world dominated by financial markets has led to the erosion of the allocation and signaling function of the interest rate, which has triggered an excessive rise of the government debt and structural distortions in the world economy. The backlash of high government debt levels on monetary policy making is argued to have led to a hysteresis of the liquidity trap. In this context, monetary reform is discussed with respect to the exit from low interest rate and high debt policies, an adaption of monetary policy rules to financial market dominated economic development, and the displacement of the prevalent world monetary system. Enhanced competition between dollar and euro as international currencies moderated by East Asia is proposed to constitute a more stable international monetary system.
urn:nbn:de:gbv:27-20131126-134300-6
Keywords: E42; E58; F33; F44; 330; Economic Instability; Credit Cycles; Monetary Policy; Hayek; Mises; Monetary Policy Rules; Monetary Policy Reform; Currency Competition; Finanzkrise; Geldpolitik; Öffentliche Schulden; Kredit; Konjunktur; Internationales Währungssystem; Reform; Währungswettbewerb; Welt